Understanding catalyst deactivation during the direct cracking of crude oil. Issue 18 (10th August 2022) - Alabdullah, Mohammed A.; Shoinkhorova, Tuiana; Dikhtiarenko, Alla; Ould-Chikh, Samy; Rodriguez-Gomez, Alberto; Chung, Sang-ho; Alahmadi, Arwa O.; Hita, Idoia; Pairis, Sébastien; Hazemann, Jean-louis; Castaño, Pedro; Ruiz-Martinez, Javier; et al.
Abstract : In the formulation of zeolite-based catalysts for the direct cracking of crude, the use of kaolin matrixes prevents, to a large extent, zeolite dealumination. Metals and other impurities in crude oil provoke a slight decrease in activity and selectivity patterns. Abstract : The increasing demand for base chemicals i.e., ethylene and propylene, along with the expected peak in gasoline and fuels demand, are stirring intense research into refineries to be built around processes that maximize the production of chemicals (oil to chemicals, OTC, processes). One of the main challenges at hand for OTC technologies is the formulation of appropriate catalysts able to handle the wide boiling point of the feed and to withstand continuous operation at industrial scale. Hydrothermal degradation, coke deposition and the presence of impurities, such as metals, sulfur and nitrogen containing species, in the feedstock affect catalyst lifetime, activity and selectivity. In this work, we evaluate long term catalyst stability along with the main causes of reversible and irreversible catalyst deactivation. Our results demonstrate that formulation prevents, to a large extent, the degradation of the zeolitic components of the catalyst. Metal deposition, on the other hand, results in a slight decrease in activity along with partial changes in selectivity patterns. The main reasons behind these changes are discussed in detail with the help of extensive characterization.